Transmigrasi dan Pembangunan di Indonesia - Wika Hardika Legiani; Ria Yunita Lestari; Haryono Haryono (Hermeneutika : Jurnal Hermeneutika, 2018)
AbstractUndang-Undang No. 15 tahun1997 concerning transmigration aims to improve the welfare of transmigrants and the surrounding community, as well as improve and make equitable development in the regions and also strengthen the unity and unity of the nation. Transmigration as a government program is very wise in overcoming population problems.Judging from the agrarian politics the transmigration program is still far from a sense of justice where 2% of Indonesia's population controls more than 90% of the territory of the Republic of Indonesia. This transmigration program is a program carried out by the government since the old order and the new order, but the process of land ownership is still not finished. Many migrants who do not yet have certificates on land that should be theirs are marked with certificates. There are still around 2 million hectares of transmigration lahars that have not been certified by the national land agency. Agrarian reform is basically a state program that is run with certain objectives, both economic (social) goals and other political and social goals. The main argument of the implementation of agrarian reform is injustice: inequality in land tenure that gives birth to poverty and leads to social injustice.Key word : transmigration and development AbstrakUndang-Undang Nomor. 15 tahun 1997 tentang ketransmigrasian bertujuan untuk meningkatkan kesejahteraan transmigran dan masyarakat sekitarnya, serta meningkatan dan melakukan pemerataan pembangunan di daerah dan juga memperkukuh persatuan dan kesatuan bangsa. Transmigrasi sebagai program pemerintah yang sangat bijak dalam mengatasi masalah kependudukan. Menilik dari politik agraria program transmigrasi masih jauh dari rasa keadilan dimana 2% dari penduduk Indonesia menguasai lebih dari 90% luas lahan wilayah Republik Indonesia. Program transmigrasi ini sebagai program yang dilakukan pemerintah sejak orde lama dan orde baru, namun proses kepemilikan lahan masih belum selesai. Banyak tansmigran yang belum memiliki sertifikat atas lahan yang seharusnya menjadi milik mereka dengan ditandai adanya setifikat. Masih ada sekitar 2 juta hektar lahar transmigrasi yang belum tersetifikat oleh badan pertanahan nasional. Reforma agraria pada dasarnya adalah program negara yang dijalankan dengan tujuan-tujuan tertentu, baik tujuan (pembangunan) ekonomi maupun tujuan politik dan sosial lainnya. Argumen pokok dari pelaksanaan reforma agraria adalah ketidakadilan: ketimpangan dalam penguasaan tanah yang melahirkan kemiskinan dan berujung pada ketitakadilan sosial.Kata Kunci : transmigrasi dan pembangunan